Global research and emerging trends in autophagy in lung cancer: a bibliometric and visualized study from 2013 to 2022 - Liu, Bo-Na; Chen, Juan; Piao, Ying (Frontiers in Pharmacology, 2024)
Purpose: To highlight the knowledge structure and evolutionary trends in research on autophagy in lung cancer. Methods: Research publications on autophagy in lung cancer were retrieved from the Web of Science Core Collection database. VOSviewer and CiteSpace data analysis software were used for the bibliometric and visualization analysis of countries, institutions, authors, journals, and keywords related to this field. Results: From 2013 to 2022, research on autophagy in lung cancer developed rapidly, showing rising trends in annual publications and citations. China (1,986 papers; 48,913 citations), Shandong University (77 publications; 1,460 citations), and Wei Zhang (20 publications; 342 citations) were the most productive and influential country, institution, and author, respectively. The journal with the most publications and citations on autophagy in lung cancer was the International Journal of Molecular Sciences (93 publications; 3,948 citations). An analysis of keyword co-occurrence showed that related research topics were divided into five clusters: (1) Mechanisms influencing autophagy in lung cancer and the role of autophagy in lung cancer; (2) Effect of autophagy on the biological behavior of lung cancer; (3) Regulatory mechanisms of two cell death processes: autophagy and apoptosis in lung cancer cells; (4) Role of autophagy in lung cancer treatment and drug resistance; and (5) Role of autophagy-related genes in the occurrence and development of lung cancer. Cell proliferation, migration, epithelial–mesenchymal transition, and tumor microenvironment were the latest high-frequency keywords that represented promising future research directions. Conclusion: This is the first comprehensive study describing the knowledge structure and emerging frontiers of research on autophagy in lung cancer from 2013 to 2022 by means of a bibliometric analysis. The study points to promising future research directions focusing on in-depth autophagy mechanisms, clinical applications, and potential therapeutic strategies, providing a valuable reference for researchers in the field.